PENINGKATAN KREATIFITAS PENGGUNAAN SOFTWARE SEBAGAI PELUANG USAHA MANDIRI PEMUDA DESA BANDA MASEN MELALUI PELATIHAN DESAIN GRAFIS - Zara Yunizar; Muhammad Daud; Said Fadhlan Anshari; Zalfie Ardian; Rizki Suwanda (LPPM Universitas Al Muslim, 2023)
One of the challenges faced by young people in rural areas is the lack of ability and creativity that can improve their standard of living in the digital era. The increasing number of university graduates and the lack of job opportunities provided by the government have the potential for a high number of unemployed people of productive age in Indonesia. This can be overcome by increasing the creative abilities of young people of productive age in creating independent business opportunities, one of which is their ability in the field of graphic design. This community service activity aimed to increase the creativity of youth in Banda Masen Village, Banda Sakti Sub-district, Lhokseumawe City in using graphic design software to develop independent business opportunities. The method used in this activity was by training and skills development approach. After identifying the needs and level of understanding of participants, graphic design training was carried out. This training focuses on introducing graphic design software, basic graphic design techniques, and applying creativity in design. The result of this community service activity was an increase in young people's skills and creativity in using graphic design software, so that they can apply these skills to open up independent business opportunities. Increased creativity and independent business opportunities provide positive economic and social impacts. Developments in the use of technology and skills at the village level can make a positive contribution to the development of society as a whole.